2019
DOI: 10.1021/jacs.9b04515
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Turnover in Artificial Enzymes via Directed Evolution Results in the Coupling of Protein Dynamics to Chemistry

Abstract: The design of artificial enzymes is an emerging field of research. Although progress has been made, the catalytic proficiency of many designed enzymes is low compared to natural enzymes. Nevertheless, recently Hilvert et al. (Nat. Chem. 2017, 9, 50-56) created a series of five artificial retro-aldolase enzymes via directed evolution, with the final variant exhibiting a rate comparable to the naturally occurring enzyme fructose 1,6 bisphosphate aldolase. We present a study of this system in atomistic detail tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 60 publications
1
34
0
Order By: Relevance
“…The molecular mechanism of the non-natural multistep retro-aldolase reaction catalyzed by a de novo enzyme, the RA95.5-5 designed by Hilvert and co-workers, 46 has been investigated by means of multiscale QM/MM methods using methodol as substrate. The results have been compared to our previous computational study on the more evolved RA95.5-8F retro-aldolase, 52 designed also by Hilvert and co-workers. 43 The obtained free energy landscape has allowed to confirm how the RA95.5-5 presents a higher overall activation free energy barrier than the RA95.5-8F (29.1 vs. 20.1 kcal mol -1 ), as well as to define the details of every of the 7 steps of the full reaction mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular mechanism of the non-natural multistep retro-aldolase reaction catalyzed by a de novo enzyme, the RA95.5-5 designed by Hilvert and co-workers, 46 has been investigated by means of multiscale QM/MM methods using methodol as substrate. The results have been compared to our previous computational study on the more evolved RA95.5-8F retro-aldolase, 52 designed also by Hilvert and co-workers. 43 The obtained free energy landscape has allowed to confirm how the RA95.5-5 presents a higher overall activation free energy barrier than the RA95.5-8F (29.1 vs. 20.1 kcal mol -1 ), as well as to define the details of every of the 7 steps of the full reaction mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Since the catalytic activity of artificial enzymes are usually much lower than that of natural enzymes, 9 several studies have been recently conducted to understand the behavior of the designed RAs, thus supporting the timeliness of the present study. 52,5354 In particular, we perform a multiscale QM/MM computational study on the reaction mechanism of the RA95.5 designed by Hilvert and co-6 workers, 48,51 and compare the results with the more evolved RA95.5-8F design, 48 previously studied in our laboratory. 54 We chose a variant showing an activity clearly lower than RA95.5-8F (see Table S1 deposited in the Supporting Information), in order to confirm the mechanism but, more importantly, to compare a less evolved RA with the most efficient one.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed Y180 has been identified as possibly serving as the catalytic base in the highly evolved RA95.5–8F. 32 , 33 A previous site‐directed mutagenesis study 9 (Table S1 ) showed that mutation of either of these two tyrosine residues individually in RA95.5–8F had a relatively modest effect on k cat / K M , while simultaneous mutation of both tyrosine residues resulted in substantially reduced activity (200‐fold loss in catalytic efficiency for the double mutant Y51F/Y180F). Note that Y51, K83, and Y180 are the three top residues in the POOL rankings for RA95.5–8F.…”
Section: Discussionmentioning
confidence: 99%
“… 23 Finally, further computational modeling identified fast time scale motions that were present only in the most catalytically efficient evolved variant of the de novo RA. 168 The change in conformational ensemble during directed evolution thus occurs as an unintentional but essential consequence of the mutations introduced during laboratory evolution.…”
Section: Enzyme Engineering By Fine-tuning Protein Conformational Dynmentioning
confidence: 99%